Factors associated with acute respiratory infection and healthcare-seeking behaviour among primary caregivers in Bangladesh: a study based on MICS 2019 - Md Fuad Al Fidah; Syeda Sumaiya Efa; Ali Amin Nabin (BMJ Publishing Group, 2024)
Introduction More than 80% of deaths due to preventable and treatable causes among under 5 (U5) children occur in the sub-Saharan Africa and the South-Asia, pneumonia remains one of the most common such causes. Bangladesh has demonstrated success in achieving the Millennium Development Goals, particularly in relation to target 4. Nevertheless, the country is still among the 10 countries with the highest number of deaths among U5 children in 2019. The current study aimed to identify factors associated with acute respiratory infections (ARIs) and the care-seeking behaviour of the children's care takes in Bangladesh.Methods The cross-sectional study used data from the Multiple Indicator Cluster Survey, Bangladesh (2019) . U5 children were included in the analysis (n=22 779). A p<0.05 as considered statistically.Results The prevalence of ARI in the past 2 weeks of survey was 2.03%. It was found that age of the child (in months), sex, residence, division, stunting, age of the mother and age of the father had statistically significant association (p<0.05). The adjusted odds ratio (AOR) of ARI were lower among older children aged 24-59 months (AOR 0.53; 95% CI 0.44 to 0.64; p<0.001), female (AOR 0.68; 95% CI 0.56 to 0.83; p<0.001) and children with father aged ≥25 years (AOR 0.61; 95% CI 0.42 to 0.88; p=0.008) and higher (AOR 1.31; 95% CI 1.07 to 1.61; p=0.010) among children with stunting. Among the children with ARI, 16.63% primary caregivers did not seek any treatment. Most of the children with ARI (65.01%) were treated with antibiotics.Conclusions The prevalence of ARI was low. However, still a significant proportion of primary caregivers of U5 children with ARI fail to seek healthcare. The proportion of U5 children who are treated with antibiotics requires attention. Focus should be on younger fathers for promoting healthcare-seeking and good feeding practice to reduce malnutrition.